Evaluasi Implementasi Kebijakan Sistem Keuangan Desa (Siskeudes) di Desa Munggu Kecamatan Ngabang Kabupaten Landak - Fuaddianto Fajar Satrio (Fakultan Ilmu Sosial dan Ilmu Politik Universitas Tanjungpura, 2020)
ABSTRACTThis study describes the result of evaluation of the implementation of the Village Financial System (SISKEUDES) policy in Munggu Village, Ngabang District, Landak Regency. This study is based on the observation and interview conducted by the author at the Village Office of Munggu Village, Ngabang District, Landak Regency where problems are found in the preparation of village financial reports using SISKEUDES.The study aims to describe and analyze the evaluation of the Implementation of the Village Financial System(SISKEUDES) Policy in Munggu Village, Ngabang District, Landak Regency.The approach used in this study isdescriptive qualitativewhilemethods for collecting data are observation, documentation and interview.The collected data will be presented by reducing unnecessary data in the study and then drawing conclusions.There are 2 (two) perspectives of the results, which are‘compliance perspective’ and ‘what’s happening perspective’.Based on the results for Compliance perspective, the implementation of the Village Financial System (SISKEUDES) policy in Munggu Village, Ngabang District, Landak Regency Is not optimal yet, it can be seen from the delay in submitting village financial report so the implementation of the policy does not go according to the plan.In addition, the existing facilities and resources in Munggu Village are inadequate for the implementation of the SISKEUDES policy.Furthermore, based on the results for What’s happening perspective, the implementation of the policy is also not optimal yet. The replacement of the SISKEUDES operator in Munggu Village affect the implementation of the SISKEUDES application because it has an impact on delays in making financial reports using the SISKEUDES application.Keywords: evaluation, implementation, Siskeudes, compliance, what’s happening